Optimization of manufacturing process for serotype 14 pneumococcal capsular polysaccharide - Li, Yuelong; Xu, Yongxue; Cao, Xin; Wang, Yanyan; Wang, Jianlong; Zhao, Yi; Wang, Hui; Yao, Hantian; Liu, Jiankai (Frontiers in Chemical Engineering, 2024)
Streptococcus pneumoniae is a pathogenic bacterium causing various infections, such as pneumonia, meningitis, otitis media and bacteremia. Prevention of pneumococcal disease by vaccination has become more urgent due to increasing antibiotic resistance. Pneumococcal capsular polysaccharides (CPSs) are effective vaccine antigens that stimulate the host to produce protective antibodies. Currently S. pneumoniae serotype 14 is one of most prevalent types in Latin America and worldwide. However, the yield of S. pneumoniae serotype 14 CPS from existing fermentation processes remains low and needs to be improved. In this study various aspects of the fermentation process were optimized to improve pneumococcal growth and polysaccharide productivity, including feed medium, cultivation gas environment, fermentation pH and temperature; in the meantime, a simplified purification method was developed to obtain pure CPS which includes ultrafiltration, acid and ethanol precipitation, diafiltration and finally lyophilization. The results demonstrated that these fermentation optimizations significantly enhanced the optical density of pneumococcal bacterial cultures and increased fermentation yield to 2.4-2.6 g/L, significantly higher than previous reports in the literature and patents.Moreover, the test results of pure CPS could meet the requirements in the European Pharmacopoeia (11 th edition). These optimizations provide valuable insights into the nutritional requirements and the impact of varying fermentation process parameters on pneumococcal growth and CPS productivity, and this will contribute to the development of a more efficient and cost-effective method for the production of pneumococcal CPSs, which is essential for the manufacturing of vaccines against pneumococcal infections.